Prospects of application of the method of real options when evaluating investment projects . (Journal of Economic Research & Business Administration, 2015)
This article discusses the prospects for applying the method of real options as a more effective method of evaluating investment projects . In particular, the article discussesthe main shortcomings of traditional methods of evaluation of investment projects , based on discounted cash flows , provides a definition of real options , a classificationreal options . Also, the example reveals the prospects of applying the method of real options for evaluation of investment projects .
Keywords: method of real options